Prevalence and Identification of Ticks in Cattle Of Rajshahi, Bangladesh (Research in Agriculture Livestock and Fisheries, 2022)
Ticks, the notorious ectoparasite, are frequently infest cattle and cause various disease conditions and acts as vector of pathogenic organism. To determine the tick infestation in cattle of four Districts of Rajshahi Division, Bangladesh, a total of 1200 cattle (300 from each district) were randomly examined throughout the year. Four hundred ticks (100 from each district) collected from cattle were microscopically identified to determine the prevalence of specific ticks. Among the examined cattle, 433 (36.08%) were found infested with one or more species of ticks. The highest prevalence was recorded in Naogaon District (39.66%) followed by Rajshahi (37.33%), Joypurhat (34.33%) and Natore (33%). Tick infestation rate was higher (p5 years) were significantly (p1-